1985
DOI: 10.1111/j.1365-2052.1985.tb01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between marker genotypes, halothane reaction, CC activity and meat quality characters in a sample of German Landrace pigs

Abstract: Routine blood typing of German Landrace pedigree populations and an earlier study revealed very low frequencies of the favourable alleles at the marker loci Phi, Pgd and H. The hypothesis was that in this population the whole linkage group of favourable alleles at the halothane and neighbouring marker loci may have been lost as a consequence of intense selection for leanness and type. The present study of 1050 German Landrace pigs at the Relliehausen experimental station, where some effort has been made to mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Further work (Christian, 1976) The association between CPK values and H blood group genotype was supported by Glodek et al (1985). Christian (1977) suggested that the H blood group was closely linked to the gene controlling PSS.…”
Section: Physiological Basismentioning
confidence: 98%
See 1 more Smart Citation
“…Further work (Christian, 1976) The association between CPK values and H blood group genotype was supported by Glodek et al (1985). Christian (1977) suggested that the H blood group was closely linked to the gene controlling PSS.…”
Section: Physiological Basismentioning
confidence: 98%
“…The S allele which allows the expression of A and 0 is dominant to the recessive allele s, which does not allow expression of the A or 0 genotypes. The S blood group genotype was often used in conjunction with the H blood group genotype to determine PSS susceptibility Christian, 1976;Christian 1977;Jorgensen, 1979;Honjy et al, 1979;Imlah and Thomson, 1979;Glodek et al, 1985). Epistasis between the S locus and the H locus was reported by Rasmusen (1972);Hojny (1974); Hojny et al…”
Section: Physiological Basismentioning
confidence: 99%